FTY720 Improves the Survival of Autologous Fat Grafting by Modulating Macrophages Toward M2 Polarization Via STAT3 Pathway. (11th October 2021) - Yi, Yi; Hu, Weijie; Lv, Wenchang; Zhao, Chongru; Xiong, Mingchen; Wu, Min; Zhang, Qi; Wu, Yiping
Autologous fat grafting (AFG) is widely regarded as an important method for breast reconstruction after mastectomy among breast cancer (BC) patients. FTY720 has been proved to affect macrophage polarization and improve the sensitivity of postoperative BC treatment. This study aimed to explore FTY720 function and underlying mechanism in fat transplantation. The C57BL/6 J mice that received AFG were randomly divided into two groups treated with saline and FTY720, respectively. The fat graft samples were obtained at week 1, 2, 4, and 12 post-transplantation. Graft volumes, graft structures, M2 macrophages, and STAT3 protein expression were estimated by histological examination, immunofluorescence, flow cytometry, and western blot, respectively. In vitro, mouse preadipocytes were stimulated with FTY720 treated-M2 macrophages conditioned medium (FTY720-M2-CM) to evaluate the adipogenesis effect. The level of adipogenic mRNA expression in preadipocytes was detected by RT-PCR. The in vivo results showed that FTY720 treatment significantly enhanced the fat graft retention, structure integrity, and neovascularization, indicating the potential of FTY720 in improving graft survival. The histology results showed more polarized M2 macrophage presented in the FTY720 group. In the in vitro assay, after FTY720-M2-CM treatment, the 3T3-L1 preadipocytes showed the increased triglyceride content and adipogenic mRNA expression, including FABP4, C/EBP-α, Adipoq, and PPARγ. Furthermore, FTY720 treatment up-regulated the expression level of M2 biomarker CD206, Arg-1, Fizz-1, which could be weakened by the STAT3 inhibitor. Together, this study confirmed the potential efficacy of FTY720 in improving graft survival in the AFG model, possibly mediated by polarizing macrophages to M2 type through activating the STAT3 pathway.